Analysis of Muslim Community Perceptions Regarding the Establishment of Non-Muslim Houses of Worship: A Qualitative Study - Milda Apriliana (Presscience, 2026)
This study examines the perceptions of Muslim communities toward the establishment of non-Muslim places of worship in Bangkala District, Jeneponto Regency. The background of the research is the social and religious homogeneity of the Muslim majority in the region, which influences their acceptance of religious diversity, especially regarding minority groups. The study aims to identify factors that shape Muslim perceptions and to explore strategies to ensure harmonious coexistence. A qualitative descriptive approach was employed, using primary data collected through interviews and observations with local government officials, religious leaders, youth figures, Muslim residents, and non-Muslim residents. Secondary data were obtained from literature, regulations, and relevant reports. The analysis involved data categorization, synthesis, and interpretation to draw meaningful conclusions. The findings indicate that Muslim perceptions are influenced by religious identity, cultural traditions, concerns about social change, location, and the intensity of worship practices by non-Muslims. Despite initial caution, the community shows conditional tolerance, particularly if non-Muslims comply with the requirements of the Ministry of Religious Affairs, including having a verified list of non-Muslim residents and support from at least 60 Muslim community members. The study suggests that open dialogue, education on religious tolerance, strategic site selection, regulatory compliance, and joint social activities can facilitate peaceful coexistence. These results have implications for local policy-making, promoting inclusive practices while respecting the dominant religious identity. The study concludes that with adherence to legal provisions and mutual respect, the establishment of non-Muslim places of worship can be managed harmoniously in a predominantly Muslim community